Multicountry clinical outcomes of a new nondiffractive presbyopia-correcting IOL. Issue 2 (February 2022) - Bala, Chandra; Poyales, Francisco; Guarro, Mercè; Mesa, Ramón Ruiz; Mearza, Ali; Varma, Devesh Kumar; Jasti, Srichand; Lemp-Hull, Jessie
Abstract : In a prospective, randomized study, the nondiffractive presbyopia-correcting IOL, DFT015, demonstrated superior intermediate and near vision, noninferior distance vision, and a similar visual disturbance profile compared with a monofocal IOL. Abstract : Purpose: To evaluate the effectiveness and safety of a new presbyopia-correcting intraocular lens (IOL) with a nondiffractive design, DFT015, compared with an aspheric monofocal IOL, SN60WF. Setting: 19 investigational sites in 4 countries: Australia, Canada, Spain, and the United Kingdom. Design: Prospective, randomized, parallel-group, controlled, assessor- and patient-masked clinical study. Methods: Participants aged ≥22 years with bilateral cataracts were randomized to DFT015 or SN60WF in a 5:4 ratio and masked until final postoperative follow-up at month 6. The primary effectiveness objective was superiority of DFT015 over SN60WF in mean monocular photopic distance-corrected intermediate visual acuity (DCIVA) at month 3. Secondary effectiveness objectives included noninferiority of DFT015 to SN60WF in mean monocular photopic corrected distance visual acuity (CDVA) and superiority in the mean monocular photopic distance-corrected near visual acuity (DCNVA) at month 3. Visual disturbances were assessed at month 6. Results: 282 patients were randomized to DFT015 (n = 159) or SN60WF (n = 123). All effectiveness objectives were achieved at month 3 in first eyes. For monocular photopic results in first eyes, DFT015 demonstrated superior mean DCIVA (least squares means of −0.139 logMAR in favor of DFT015, P < .001), noninferior mean CDVA (97.5% upper confidence limit [UCL] of the difference was <0.1 logMAR) and superior mean DCNVA (95% UCL of the difference was <0.0 logMAR) compared with SN60WF at month 6. DFT015 exhibited a similar visual disturbance profile to that of SN60WF. Conclusions: DFT015 provided superior intermediate and near vision and a similar visual disturbance profile compared with an aspheric monofocal IOL.